Analisis Kesalahan Berbahasa Indonesia dalam Whatsapp Mahasiswa Fakultas Ilmu Kesehatan Program Studi Farmasi Angkatan 2023 dengan Dosen MKDU Universitas dr. Soebandi - Setyorini Dwi Agustini; Siti Yuliana; Hamliyah Hamliyah (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Whatsapp is always used in communication at this time. Lecturers and students also use the application to communicate about lectures. However, there are still many mistakes in writing messages in whatsapp. The objectives of this study are 1) To describe and explain capitalization errors, 2) Describe and explain the forms of errors in writing punctuation dots (.), commas (,), question (?), exclamation points (!), colons (:), quotation marks ("), and conjunctions (-), 3) Describe and explain the forms of word writing errors in whatsapp Students of the Faculty of Health Sciences Pharmacy Study Program Batch 2023 with MKDU Lecturers at Dr. Soebandi University. This research uses qualitative descriptive method. The stages are 1) determining the research setting, 2) determining the research method, 3) collecting data, 4) analyzing data, 5) checking data validity, 6) data exposure and data findings exposure. The results of the study showed 789 language errors in the writing of punctuation and spelling in whatsapp students of the Faculty of Health Sciences Pharmacy Study Program Batch 2023 with MKDU Lecturers at Dr. Soebandi University. These errors are classified into capitalization errors as much as 357 data, then language errors in punctuation writing, namely period (.) 159 data, comma (,) 37 data, question mark (?) 11 data, exclamation mark (!) 3 data, colon (:) 1 data, double quotation mark (") 2 data, hyphen (-) 6 data, and language errors in writing words (abbreviations, re-forms, regional languages, and foreign languages) as much as 213 data.